Can I Be Who I Am? Psychological Authenticity Climate And Employee Outcomes. Issue 1 (1st January 2022) - Ostermeier, Kathryn; Cooper, Danielle; Caldas, Miguel
ABSTRACT: We propose and test the construct of psychological authenticity climate, which we define as a psychological climate where employees perceive that their organization encourages and provides a safe environment for them to express their personal identities at work. Through a 4-study design spanning two countries (United States and Brazil), we establish relationships between psychological authenticity climate and organizationally relevant employee outcomes. In Study 1 and Study 2 we assess the measurement validity of our proposed measure. In Studies 3a and 3b ( n = 282; n = 188), we assess the predictive validity of our construct and test our hypothesized model across two time points. Results indicate overall support for our model, with psychological authenticity climate affecting key outcomes like organizational citizenship behaviors (OCBs), job satisfaction, and job burnout through organizational identification (OID).